Students' Perception on Public Speaking Lecture for Their Speaking Ability - Sulis Liani; Heni Novita Sari (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this study is to identify students’ perception on public speaking lecture for their speaking ability. The writer used a qualitative descriptive design to provide an overview of information obtained from the data. A sample of 10 students of fourth-semester students from the English Education Department in the Academic Year 2021/2022 who are studying Public Speaking Lectures will take part in this study. The interviews were the process of obtaining information for research by way of questions and answers while looking face to face respondents using an interview guide. An interactive model of analysis was used to analyze the data in this study. The results of student perceptions fou`1%nd that students stated that public speaking lecture is very influential on their speaking ability, the use of public speaking lecture can also make them more able to express their feelings, students can explore and increase their vocabulary, and influence people with their words.